1995
DOI: 10.1080/14640749508401385
|View full text |Cite
|
Sign up to set email alerts
|

On the Interaction of Prior Knowledge and Stimulus Structure in Category Learning

Abstract: Contemporary theories of categorization propose that concepts are coherent in virtue of being embedded in a network of theories about the world. Those theories function to pick out some of the many possible features of a set of objects as most salient for purposes of classification, a process that is complex and still poorly understood (Murphy & Medin, 1985). Part of what makes this account incomplete is a lack of information as to (1) what makes a feature salient on a given occasion and (2) how feature salien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Categorization can also be acquired by selectively attending to the relevant dimension along which the categories differ (Nosofsky, 1984) or to certain features by which they differ (Livingston & Andrews, 1995). Categorization may also occur through a process called differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Categorization can also be acquired by selectively attending to the relevant dimension along which the categories differ (Nosofsky, 1984) or to certain features by which they differ (Livingston & Andrews, 1995). Categorization may also occur through a process called differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…More recently Medin et al (1993) have shown that how a dimension of variation is coded for purposes of establishing similarity depends on what portion of the dimension is available for examination. Livingston and Andrews (1995) have demonstrated that whether a particular dimension is salient for a classification may depend on how instances that vary on that dimension are presented to the concept learner. These results, among others, suggest that whether a given pair of items is identified as belonging to the same category depends upon the contrast set within which they are encountered.…”
Section: Concept Acquisition and Use Occurs In (Real) Contextmentioning
confidence: 99%
“…The concepts we have acquired prior to that encounter, along with our goals and purposes at the time, also matter. The human capacity to control the direction of attention makes it possible to treat some members of a set to the exclusion of others, thereby changing the (psychological) context of potentially confusable alternatives and altering the relative salience and judged importance of various dimensions of variation (see, e.g., Livingston & Andrews 1995;Medin et al 1997). These selections constitute hypotheses about which groupings will be the right ones for our purposes, and are tested in various ways against facts about the consequences of deploying the concept-in-the-making in pursuit of those purposes.…”
Section: Concept Acquisition and Use Occurs In (Real) Contextmentioning
confidence: 99%
“…Another is that the feature set itself is actually fixed, but that the ranking or relative importance of features can be affected by learning and experience (e.g. Haider & Frensch, 1996; Livingston & Andrews, 1995). It is not clear how, or even if, it is possible to distinguish between these two interpretations of the flexibility view.…”
Section: Introductionmentioning
confidence: 99%